Effect of Current Asset Structure on Financial Performance of Non-Financial Firms Listed at Nairobi Securities Exchange - Obong’o, Simeon Mochere; Nasieku, Tabitha; Gekara, Mouni (Journal of Business Management and Economic Development, 2024)
The effect of current asset structure on the financial performance on organizations cannot be underrated. This study focused on non-financial firms listed at the Nairobi Securities Exchange in Kenya. The study used a census survey which involved the consideration of the entire population of the study. The research study was anchored on trade-off theory, agency theory and pecking order theory. The research study generally followed a longitudinal research design. The positivism research philosophy was adopted in the study. The unit of analysis comprised the non-financial firms listed at the Kenyan NSE between years 2011 to 2020 with a focus on 30 non-financial listed companies. The study applied both descriptive statistics and multiple regression methods in analysing the data collected. The study established that current asset structure was significantly influencing the financial performance of listed nonfinancial firms in Kenya.